Megan Meade's guide to the McGowan boys - Brian, Kate, 1974- (New York : Simon Pulse, 2006)
While her military parents are stationed in South Korea, high school junior Megan learns a great deal about boys and herself when she moves to Massachusetts to live with family friends who have seven sons.
Accelerated Reader AR
Keywords: Interpersonal relations -- Juvenile fiction; Self-confidence -- Juvenile fiction; Brothers -- Juvenile fiction; High schools -- Massachusetts -- Juvenile fiction